2006
DOI: 10.1016/j.jphotochem.2005.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-assisted intramolecular vibrational energy redistribution of S1 perylene in ketone solvents

Abstract: We investigated vibrational energy relaxations of S 1 perylene at an excess energy of ca. 2800 cm -1 in several ketone solvents by femtosecond time-resolved fluorescence measurements.Temporal evolution of fluorescence emissions occurs on the following distinct timescales: 70 ~ 330 fs, 0.6 ~ 1.1 ps and 1.8 ~ 4.9 ps. The latter two was assigned to the intramolecular vibrational redistribution (IVR), and to the solvent-assisted IVR (SA-IVR), respectively. In SA-IVR, intramolecular vibrational couplings are affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
(55 reference statements)
3
25
0
Order By: Relevance
“…Similarly in solution, while solvent induced effects could be estimated using force field MD simulations, 56 typically direct energy transfer can occur on the same timescale of about 10 ps, [57][58][59][60] so it is difficult to disentangle from solvent-mediated IVR, which can occur on the timescale of about 1 ps. 54,[61][62][63][64][65] The reported results provide fundamental understanding of energy transfer that may limit the effectiveness of catalysts mounted on metals. Diminished vibrational lifetimes due to EHPs will negatively affect the ability to modify bonds.…”
Section: System A'(1) A''/a'(2)mentioning
confidence: 91%
“…Similarly in solution, while solvent induced effects could be estimated using force field MD simulations, 56 typically direct energy transfer can occur on the same timescale of about 10 ps, [57][58][59][60] so it is difficult to disentangle from solvent-mediated IVR, which can occur on the timescale of about 1 ps. 54,[61][62][63][64][65] The reported results provide fundamental understanding of energy transfer that may limit the effectiveness of catalysts mounted on metals. Diminished vibrational lifetimes due to EHPs will negatively affect the ability to modify bonds.…”
Section: System A'(1) A''/a'(2)mentioning
confidence: 91%
“…The delay time Δt 1 should be long enough to allow the termination of the ring-closure reaction ( Δt 1 > 1 ps) and should extend until the end of the vibrational redistribution times. For polyatomic molecules with a size similar to fulgides, intramolecular vibrational redistribution occurs in the range of a few picoseconds19, 20 and heat transfer to the surrounding solvent occurs on the time scale of 10 ps 21, 22. Therefore, a time range for Δt 1 between 2 and 50 ps is used which allows access to different vibrational populations of the C -isomer ground state.…”
Section: The Trifluorinated Indolylfulgidementioning
confidence: 99%
“…The former is an intramolecular relaxation of the initial non-uniform vibrational energy distribution, and the latter is an intermolecular energy transfer process leading to thermal equilibrium. Recent ultrafast time-resolved studies of VR have revealed that both IVR and VC may occur via sequential mechanisms in liquid solutions [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%